Peran Sistem Informasi Manajemen dalam Mendukung Strategi Mutu dan Efektivitas Fasilitas Pelayanan Kesehatan - Firman Bintara Maju Harianja (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Management Information Systems (MIS) play an important role in supporting quality improvement and organizational effectiveness in healthcare facilities. This study aimed to analyze the role of Management Information Systems in supporting quality strategies and effectiveness of healthcare service facilities in Mukomuko Regency. This research employed a quantitative method with an observational analytic design. The population consisted of healthcare workers and administrative staff in healthcare facilities in Mukomuko Regency, with a total sample of 92 respondents selected using a total sampling technique. Data were collected through structured questionnaires and analyzed using descriptive statistics, Pearson correlation tests, and linear regression analysis.The results showed that the implementation of Management Information Systems in healthcare facilities in Mukomuko Regency was categorized as good. The quality strategy and effectiveness of healthcare facilities were also predominantly in the good category. Statistical analysis revealed a positive and significant relationship between Management Information Systems and healthcare quality strategies (r = 0.63; p < 0.05), as well as between Management Information Systems and organizational effectiveness (r = 0.66; p < 0.05). Furthermore, Management Information Systems had a significant effect on quality strategies and effectiveness, contributing 39% and 43%, respectively.In conclusion, Management Information Systems play a significant role in supporting quality strategies and organizational effectiveness of healthcare service facilities in Mukomuko Regency. Therefore, strengthening the implementation of Management Information Systems through system improvement and enhancement of human resource competencies is necessary to support high-quality and effective healthcare services.